Association between redox biomarkers, DNA damage and aerobic capacity before and after physical stress in young men - Daniela Weber; Jonas Thimm; Tamina Seiz; Bastian Kochlik; Jana Raupbach; Alexander Bürkle; Tilman Grune; Markus Gruber; Maria Moreno-Villanueva (Redox Biology)
The interaction of reactive molecules with proteins, lipids and carbohydrates results in the formation of compounds generally called redox biomarkers. It is widely recognized that high intensity exercise results in an increase of oxidative stress which in turn induces DNA damage. However, aerobic trained individuals seem to be less affected than untrained individuals. We previously showed that exercise-induced DNA damage is indeed higher in untrained individuals compared with trained individuals. But to which extent redox biomarkers are associated with DNA damage and how both are associated with aerobic capacity remains unclear. Therefore, we measured well-established redox biomarkers in plasma from young healthy volunteers before and after exhaustive exercise. We found that aerobic capacity, as measured by the level of VO2 peak, is negatively associated with glyoxal, methylglyoxal and 3-deoxyglucosone concentration in plasma before and after exhaustive physical exercise. In contrast, protein carbonyls, 3-nitrotyrosine and malondialdehyde were not associated with aerobic capacity. Interestingly, glyoxal was positively associated with DNA strand breaks in immune cells before but not after exhaustive exercise, indicating a beneficial effect of a high aerobic capacity on DNA integrity. These results provide a potential mechanism of how exercise protects against cardiovascular diseases, diabetes and cancer development.